2020
DOI: 10.1136/bmjopen-2019-030267
|View full text |Cite
|
Sign up to set email alerts
|

Does an emergency access button increase the patients’ satisfaction and feeling of safety with the out-of-hours health services? A randomised controlled trial in Denmark

Abstract: ObjectiveTo investigate if the option to bypass the telephone queue can increase satisfaction and feeling of safety in callers.DesignRandomised controlled parallel superiority trial. Data from questionnaire survey.SettingTwo out-of-hours (OOH) services in Denmark.Participants217 510 citizens who called the OOH services between 4 September 2017 and 30 November 2017.RandomisationTwo-faze study period: First half with randomisation of participants based on their date of birth; even date randomised to intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…However, departments must first determine if they need AI to estimate wait times before proceeding. If the waiting time in the department is unusually short or the patient’s willingness for use AI is low, then there is no urgent need to predict the waiting time ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, departments must first determine if they need AI to estimate wait times before proceeding. If the waiting time in the department is unusually short or the patient’s willingness for use AI is low, then there is no urgent need to predict the waiting time ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is also common in other healthcare settings, where patients described how they felt safer knowing nurses were nearby, watching over them and having everything under control (Gettens et al, 2018; Lovink et al, 2015), or when they knew they could use the call button if they needed help (Watson et al, 2021). In this sense, Ebert et al (2020) studied the out‐of‐hours services in Denmark which provided telephone advice for citizens with acute but non‐life‐threatening health problems, and concluded that the option of bypassing the telephone queue increased satisfaction and feelings of safety in callers (Ebert et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Ebert et al (2020) studied the out-of-hours services in Denmark which provided telephone advice for citizens with acute but non-life-threatening health problems, and concluded that the option of bypassing the telephone queue increased satisfaction and feelings of safety in callers (Ebert et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research methods used to write this article: economic-statistical analysis and synthesis, graphical method, analysis of series of dynamics [17]. Previously, it has been proved that research is more profitable in terms of financial and time aspects using electronic platforms [18]. Therefore, informational data for the article was taken from the website of the National Bank of the Republic of Kazakhstan.…”
Section: Metodologymentioning
confidence: 99%